2014
DOI: 10.1186/s12918-014-0112-4
|View full text |Cite
|
Sign up to set email alerts
|

Autocrine FGF feedback can establish distinct states of Nanog expression in pluripotent stem cells: a computational analysis

Abstract: BackgroundThe maintenance of stem cell pluripotency is controlled by a core cluster of transcription factors, NANOG, OCT4 and SOX2 – genes that jointly regulate each other’s expression. The expression of some of these genes, especially of Nanog, is heterogeneous in a population of undifferentiated stem cells in culture. Transient changes in expression levels, as well as heterogeneity of the population is not restricted to this core regulator, but involve a large number of other genes that include growth factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“…The heterogeneity is dynamically maintained, with individual cells exhibiting transient changes in expression levels. Nanog heterogeneity has been widely studied by mathematical modeling approach and it was shown that the phenomenon may be inferred from properties of OSN interaction circuit, activity of signal transduction pathways or transcriptional stochasticity induced transitions [ 12 , 36 , 40 , 43 , 76 ]. Our model also describes this behavior in domains D 2 and D 3 , in which all revealed states are unstable ( Fig 3A ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The heterogeneity is dynamically maintained, with individual cells exhibiting transient changes in expression levels. Nanog heterogeneity has been widely studied by mathematical modeling approach and it was shown that the phenomenon may be inferred from properties of OSN interaction circuit, activity of signal transduction pathways or transcriptional stochasticity induced transitions [ 12 , 36 , 40 , 43 , 76 ]. Our model also describes this behavior in domains D 2 and D 3 , in which all revealed states are unstable ( Fig 3A ).…”
Section: Resultsmentioning
confidence: 99%
“…Comparing sustained oscillations and stochastic fluctuations in an agent-based model suggested that the noise-driven model more consistently explain Nanog expression dynamics in mESC populations. Coupling in simulations the OSN network to extracellular signals provided evidence that stochastic autocrine feedback loops might also generate fluctuations in Nanog expression [ 43 ]. Meanwhile, a single-molecule fluorescent in situ hybridization used to detect Nanog mRNA in mESCs, cultured in serum/LIF or 2i/LIF media, offered evidence for the stochastic nature of Nanog expression in pluripotent mESCs, independently of the culture conditions implying that NANOG fluctuations are not dependent on autocrine ERK signaling mediated by FGF4 [ 44 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been proposed that Epi fate reinforces PrE fate in neighbouring cells via FGF4 in mid blastocysts 4,22,45,46 . NANOG expressing cells would secrete FGF4, inducing GATA6 expression in the neighbouring cells.…”
Section: Higher Levels Of Nanog In a Cell Do Not Instruct Its Direct mentioning
confidence: 99%
“…Interactions between the core network genes Nanog, Oct4 and Sox2 were kept the same as in, 31 where the authors considered the Oct4-Sox2 heterodimer complex, 40 rather than the two single genes, regulating Nanog. Modelling the former regulation only has already been proven to enable good reproduction of mESC dynamics in serum/LIF 30 , 31 , 41 44 and reduces the number of unknown parameters in the model. In the NIA bank analysis we found that Oct4 represses Nanog; consistently, in our network, the complex both activates Nanog, 40 and also indirectly represses Nanog via the Fgf/Erk module (see below).…”
Section: Resultsmentioning
confidence: 99%